2006
DOI: 10.1111/j.1439-0523.2006.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparative analysis of quantitative trait loci associated with parthenocarpy in processing cucumber

Abstract: Parthenocarpy (seedless fruit) is an economically important yieldrelated trait in cucumber (Cucumis sativus L.; 2n ¼ 2x ¼ 14). However, the genomic locations of factors controlling parthenocarpic fruit development in this species are not known. Therefore, an F 2 : 3 mating design was utilized to map quantitative trait loci (QTL) for parthenocarpy using a narrow cross employing two gynoecious, indeterminate and normal leaf lines [2A (parthenocarpic) and Gy8 (non-parthenocarpic)]. QTL detection was performed emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…This finding contrasts with those of Hawthorn and Wellington (1930) and Pike and Peterson (1969) who suggested that the inheritance of parthenocarpy in US processing cucumber is controlled by a single major gene. To gain more insight into the number of genes controlling parthenocarpy, a quantitative trait loci (QTL) analysis has recently been conducted that identified several genes (approximately 8 QTL) for parthenocarpy in the 2A × Gy8 population (Sun et al. 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with those of Hawthorn and Wellington (1930) and Pike and Peterson (1969) who suggested that the inheritance of parthenocarpy in US processing cucumber is controlled by a single major gene. To gain more insight into the number of genes controlling parthenocarpy, a quantitative trait loci (QTL) analysis has recently been conducted that identified several genes (approximately 8 QTL) for parthenocarpy in the 2A × Gy8 population (Sun et al. 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…[14,23,19] found the importance of using molecular DNA indicators in improving the quality and productivity of cucumber. [21,7,10,25] confirm the importance of molecular DNA indicators in forming genetic link maps of cucumber. [24] identifiedthe sites of genes, that responsible of parthenocarpy in cucumber, by using molecular DNA indicators.…”
Section: Introductionmentioning
confidence: 81%
“…Cucumber genetic maps have been constructed using narrow-and broad-based populations (Bradeen et al 2001;Fazio et al 2003;Sun et al 2006a;Yuan et al 2008). However, genetic mapping of economically important traits has not been performed using Beit Alpha cucumber germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage groups F1, F2, F3, F4, F5, F6, and F6 are fromFazio et al (2003); linkage groups S1, S2, S3, S4, S5, S6, and S7 are fromSun et al 2006a; linkages groups Y1, Y2, Y3, Y4, Y5, Y6, and Y6 are fromYuan et al (2008) b BC 1 indicates markers used during the marker assisted selection (MAS) of the BC 1 generation c BC 2 indicates markers used during MAS of the BC 2 generation d Yes indicates the use of that marker during selection or evaluation, No indicates the exclusion of the marker e Expected allele frequency of the homozygous genotype of the recurrent parent in the BC 2 S 3 generation f Observed allele frequency towards the homozygous genotype of the recurrent parent at BC 2 S 3 generation…”
mentioning
confidence: 99%